2012
DOI: 10.1128/jcm.05996-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Idaho Technology FilmArray System to Real-Time PCR for Detection of Respiratory Pathogens in Children

Abstract: The FilmArray Respiratory Panel (RP) multiplexed nucleic acid amplification test (Idaho Technology, Inc., Salt Lake City, UT) was compared to laboratory-developed real-time PCR assays for the detection of various respiratory viruses and certain bacterial pathogens. A total of 215 frozen archived pediatric respiratory specimens previously characterized as either negative or positive for one or more pathogens by real-time PCR were examined using the FilmArray RP system. Overall agreement between the FilmArray RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 32 publications
(28 reference statements)
8
101
1
1
Order By: Relevance
“…These findings suggest that the discordant results were frequently reported in samples containing low viral copy. Other studies also indicated that discrepant results between RV assay was quite associated with sample's viral load 7, 8, 19, 20, 21. One samples by AP and three samples by AD identified as INF A positive by additional testing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings suggest that the discordant results were frequently reported in samples containing low viral copy. Other studies also indicated that discrepant results between RV assay was quite associated with sample's viral load 7, 8, 19, 20, 21. One samples by AP and three samples by AD identified as INF A positive by additional testing.…”
Section: Discussionmentioning
confidence: 97%
“…Performance evaluation studies for newly developed multiplex RV kits are weak, do not establish the reference standard method and therefore do not sufficiently calculate sensitivity and specificity of each test. Instead, some studies have suggested the reference test with in‐house multiplex real‐time PCR or commercial duplex PCR tests 5, 6, 7, 8. We performed a direct comparison of three commercial multiplex assays and produced the values of the agreement and kappa instead of sensitivity and specificity with the reference tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is less likely that a listed tested virus was present and missed, as the PCR testing has .92% sensitivity for each tested virus, except certain adenovirus serotypes. 17 It should be noted that severe complications were not significantly more common among children without virus identified. Additionally, although we were able to perform subanalyses for pandemic H1N1 infection, the analyses were limited because of sample size.…”
Section: Figurementioning
confidence: 99%
“…17 Specific viruses identified included influenza A and B, parainfluenza viruses, rhinovirus, human metapneumovirus, adenovirus, and respiratory syncytial virus (RSV). Results of multiplex viral respiratory PCR testing were collected after the ED visit was complete.…”
Section: Virology and Microbiologymentioning
confidence: 99%
“…In the study by Pierce et al, the sensitivity of Filmarray RP version 1.6 was 46% compared to standard individual real-time quantitative PCR assays (13,14). Among the currently FDA-approved molecular assays that detect more than 3 respiratory pathogens, the sensitivity for detection of ADV ranges from 57.1% to 100%; with a sensitivity of 57.1% reported for FilmArray RP v1.6 (13,14). The low sensitivity of FilmArray RP v1.6 for ADV specifically relates to ADV C, serotypes 2 and 6 (13).…”
mentioning
confidence: 99%